MARKETING STRATEGY ANALYSIS TO INCREASE MSME COMPETITIVENESS (Study on Convection Business in Medan Denai District) - Feby Aulia Safrin; Onan Marakali Siregar; Ainun Mardhiyah Ainun (SEAN Institute, 2022)
Micro, small and medium enterprises (MSMEs) are one of the spearheads of a country's economy. The development of MSMEs, especially in Indonesia, continues to grow from year to year, one of the MSMEs that continues to grow is the textile and textile product processing sector (TPT) or commonly known as the convection business. The great prospect makes competition in this sector even tighter, so that convection business actors must have a strategy that can be used to compete, one of which is using a marketing strategy. This study aims to identify and analyze the marketing strategies used by the convection business in Medan Denai District in carrying out business activities in making clothing products so that they can compete with similar businesses. The research method used is descriptive research with a qualitative approach. Data collection techniques were obtained from both primary and secondary data. Meanwhile, secondary data was obtained through related agency data and literature study. The data analysis technique used is the SWOT method.The results of the study show that MSMEs in Medan Denai Sub-district in their marketing strategy apply a marketing mix strategy in marketing their products, namely through product strategies, pricing strategies, distribution channel strategies and promotional strategies. To win the competition with similar businesses, MSMEs in Medan Denai District can use a combination of SO (strength opportunity) strategies, namely by expanding market share, improving the quality of human resources, improving product and service quality and maximizing promotions